Interaction Mechanisms Between Major Depressive Disorder and Non-alcoholic Fatty Liver Disease - Shao, Qi; Wu, Yiping; Ji, Jing; Xu, Tian; Yu, Qiaoyu; Ma, Chongyang; Liao, Xuejing; Cheng, Fafeng; Wang, Xueqian (Frontiers in Psychiatry, 2021)
Major depression(MD) is highly related to nonalcoholic fatty liver disease(NAFLD), with complex pathogenic mechanism. However, there are few cross-sectional studies on the mechanism of MD and NAFLD mutual pathogenesis. Through the summary of this article, we find that the chronic rise of glucocorticoid(GC) caused by chronic stress plays an important role in MD-related NAFLD. The increase of GC can induce the release of inflammatory factors and the change of gut permeability, and the increased inflammatory factors mediate the activation of the Hypothalamic-pituitary-adrenal(HPA) axis, which further increases the release of GC. At the same time, the change in gut permeability further promotes the release of inflammatory factors, which forms a vicious circle among the three, causing disease outbreaks. Although the specific role of thyroid hormone(TH) in this pathogenesis is unclear, it is highly correlated with MD and NAFLD. Therefore, changing lifestyles and reducing psychological stress are necessary measures to prevent MD-related NAFLD. Among them, GC inhibitors and receptor antagonists may be the key to cutting off early and mid-term disease deterioration. The combination medication may be a good choice when the disease further develops, but it needs further research about how to avoid the side effects caused by the combination medication. However, the development of traditional Chinese medicine makes it possible to treat such complex diseases.